Emerging palaeoecological frameworks for elucidating plant dynamics in response to fire and other disturbance. Issue 1 (27th October 2021) - Napier, Joseph D.; Chipman, Melissa L.
Abstract: Motivation: Rapid climate change is altering plant communities around the globe fundamentally. Despite progress in understanding how plants respond to these climate shifts, accumulating evidence suggests that disturbance could not only modify expected plant responses but, in some cases, have larger impacts on compositional shifts than climate change. Climate‐driven disturbances are becoming increasingly common in many biomes and are key drivers of vegetation dynamics at both species and community levels. Palaeoecological records provide valuable observational windows for elucidating the long‐term impacts of these disturbances on plant dynamics; however, sparse resolution and difficulty in disentangling drivers of change limit our ability to understand the impact of disturbance on plant communities. In this targeted review, we highlight emerging opportunities in palaeoecology to advance our understanding about how disturbance, especially fire, impacts the ecological and evolutionary dynamics of terrestrial plant communities. Location: Global examples, with many from North America. Conclusions: We propose a set of palaeoecological and integrative approaches that could greatly enhance our understanding of how disturbance regimes influence global plant dynamics. Specifically, we identify four future study areas: (1) focus on palaeoecological disturbance proxies beyond fire and leverage multi proxy research to examine the influence of interacting disturbances on plant community dynamics; (2) use advances in disturbance and vegetation reconstructions, including ancient sedimentary DNA, to provide the spatial, temporal and taxonomic resolution needed to resolve the relationship between changing disturbance regimes and corresponding shifts in plant community composition; (3) integrate palaeoecological, archaeological and Indigenous knowledge to disentangle the complex interplay between climate, human land use, fire and vegetation structure; and (4) apply "functional palaeoecology" and the synergy between palaeoecology and genetics to understand how fire disturbance has served as a long‐standing selective agent on plants. These frameworks could increase the resolution of disturbance‐driven plant dynamics, potentially providing valuable information for future management.